Activation of Human Mesenchymal Stem Cells Impacts Their Therapeutic Abilities in Lung Injury by Increasing Interleukin (IL)‐10 and IL‐1RN Levels. (2nd October 2013) - Bustos, Martha L.; Huleihel, Luai; Meyer, Ernest M.; Donnenberg, Albert D.; Donnenberg, Vera S.; Sciurba, Joseph D.; Mroz, Lyle; McVerry, Bryan J.; Ellis, Bryon M.; Kaminski, Naftali; Rojas, Mauricio
Abstract : The objective of this study was to improve the protective anti‐inflammatory capacity of human mesenchymal stem cells (hMSCs) by evaluating the consequences of preactivating them before use in a murine model of acute respiratory distress syndrome. It was found that the immunomodulatory capacity was better in hMSCs obtained with minimal manipulation, showing that it is possible to improve the protective anti‐inflammatory capacity of hMSCs. Abstract : Acute respiratory distress syndrome (ARDS) is an important cause of morbidity and mortality, with no currently effective therapies. Several preclinical studies have shown that human mesenchymal stem cells (hMSCs) have therapeutic potential for patients with ARDS because of their immunomodulatory properties. The clinical use of hMSCs has some limitations, such as the extensive manipulation required to isolate the cells from bone marrow aspirates and the heterogeneity in their anti‐inflammatory effect in animal models and clinical trials. The objective of this study was to improve the protective anti‐inflammatory capacity of hMSCs by evaluating the consequences of preactivating hMSCs before use in a murine model of ARDS. We injected endotoxemic mice with minimally manipulated hMSCs isolated from the bone marrow of vertebral bodies with or without prior activation with serum from ARDS patients. Minimally manipulated hMSCs were more efficient at reducing lung inflammation compared with isolated and in vitro expanded hMSCs obtained from bone marrow aspirates. Where the most important effect was observed was with the activated hMSCs, independent of their source, which resulted in increased expression of interleukin (IL)‐10 and IL‐1 receptor antagonist (RN), which was associated with enhancement of their protective capacity by reduction of the lung injury score, development of pulmonary edema, and accumulation of bronchoalveolar lavage inflammatory cells and cytokines compared with nonactivated cells. This study demonstrates that a low manipulation during hMSC isolation and expansion increases, together with preactivation prior to the therapeutic use of hMSCs, would ensure an appropriate immunomodulatory phenotype of the hMSCs, reducing the heterogeneity in their anti‐inflammatory effect.